Five-factor model of personality disorders: Spanish normative data and validation - Colodro, Joaquín; López-García, Juan J.; Mezquita, Laura; Colodro-Conde, Lucía; Ibáñez, Manuel I.; Edo, Silvia; Villa, Elena; Ortet, Generós (Anales de Psicología / Annals of Psychology, 2018)
The categorical approach of personality disorders (PD) has given way to a dimensional paradigm. Within this, the Five-factor model (FFM) proposes theoretical hypotheses describing personality pathologies and PD empirical prototypes based on the DSM (DSM-PD). Moreover, a methodology to score DSM-PD using the NEO PI-R facets was developed. In this ex post-facto study FFM-PD count norms were developed using data from the NEO PI-R Spanish adaptation. Furthermore, the diagnostic agreement with the IPDE and validity of FFM-PD counts was analyzed in a clinical (n = 222) and non-clinical sample (n = 742). Based on NEO PI-R scores, we presented Spanish FFM-PD normative data. FFM-PD benchmarks were highly likely to be exceeded if subjects were classified as a subclinical case in the DSM-PD. Convergent correlations of FFM-PD counts with their equivalent subclinical cases of DSM-PD were statistically significant and outperformed any divergent correlation as well as the average divergent correlations in all FFM-PD. The use of a count technique based on NEO PI-R facets and Spanish FFM-PD normative data facilitate PD understanding and interpretation in various applied psychology fields.